Somatic Mutations Modulate Autoantibodies against Galactose-Deficient IgA1 in IgA Nephropathy - Huang, Zhi Qiang; Raska, Milan; Stewart, Tyler J; Reily, Colin; King, R Glenn; Crossman, David K; Crowley, Michael R; Hargett, Audra; Zhang, Zhixin; Suzuki, Hitoshi; Hall, Stacy; Wyatt, Robert J; et al. (Journal of the American Society of Nephrology, 2016)
Autoantibodies against galactose-deficient IgA1 drive formation of pathogenic immune complexes in IgA nephropathy. IgG autoantibodies against galactose-deficient IgA1 in patients with IgA nephropathy have a specific amino-acid sequence, Y1CS3, in the complementarity-determining region 3 of the heavy chain variable region compared with a Y1CA3 sequence in similar isotype-matched IgG from healthy controls. We previously found that the S3 residue is critical for binding galactose-deficient IgA1. To determine whether this difference is due to a rare germline sequence, we amplified and sequenced the corresponding germline variable region genes from peripheral blood mononuclear cells of seven patients with IgA nephropathy and six healthy controls from whom we had cloned single-cell lines secreting monoclonal IgG specific for galactose-deficient IgA1. Sanger DNA sequencing revealed that complementarity-determining region 3 in the variable region of the germline genes encoded the Y1C(A/V)3 amino-acid sequence. Thus, the A/V>S substitution in the complementarity-determining region 3 of anti-galactose-deficient-IgA1 autoantibodies of the patients with IgA nephropathy is not a rare germline gene variant. Modeling analyses indicated that the S3 hydroxyl group spans the complementarity-determining region 3 loop stem, stabilizing the adjacent β-sheet and stem structure, important features for effective binding to galactose-deficient IgA1. Understanding processes leading to production of the autoantibodies may offer new approaches to treat IgA nephropathy.
Keywords: mutace; Galactose; IgA nephropathy; Humans; lidé; immunology; Immunoglobulin A; IgA nefropatie; Mutation; galaktosa; Autoantibodies; immune complexes; Glomerulonephritis, IGA; imunoglobulin A; autoprotilátky